Dehumanization Metaphors in Heavy Metal Lyrics: Their Impact on L2 Learners’ Vocabulary and Critical Discourse Skills - Hartono, Budhi (English Education Department, 2025)
This study investigates how dehumanization metaphors in heavy metal lyrics specifically Slipknot’s Iowa (2001) influence L2 learners’ vocabulary acquisition and critical discourse skills. Although extreme metal lyrics are often perceived as violent or non-academic, they offer rich linguistic input containing complex metaphors, emotional intensity, and identity-based discourse. Using a qualitative descriptive design, fifteen intermediate EFL learners analyzed three Slipknot songs (“People = Shit,” “The Heretic Anthem,” and “Disasterpiece”) through the lens of Critical Discourse Analysis (CDA). Data were obtained through pre–post vocabulary tests, CDA worksheets, reflective journals, and semi-structured interviews. The findings indicate a significant improvement in learners’ mastery of advanced vocabulary, particularly metaphorical and emotionally laden lexical items. The analysis of extreme metaphors encouraged deep processing, fostering greater retention and contextual understanding. Moreover, students demonstrated enhanced critical discourse awareness, including the ability to identify ideological meanings, decode violent metaphors symbolically, and interpret identity construction within the lyrics. Emotional engagement with the material also contributed positively to motivation and learning outcomes. Overall, the study concludes that heavy metal lyrics when approached critically serve as effective authentic materials for developing higher-order linguistic and analytical competencies in SLA. Such texts not only expand vocabulary and discourse skills but also support learners’ identity development by enabling them to explore themes of alienation, resistance, and self-expression through language.